Lignoids in seedlings of Virola sebifera - Danelutte, Ana Paula; Cavalheiro, Alberto José [UNESP]; Kato, Massuo Jorge (My University, 2000)
Quantitative analysis carried out by high performance liquid chromatography indicated the accumulation of a major secondary compound in seedlings of Virola sebifera which was isolated and identified as the lignan hydroxy-otobain. This lignan occurs only in trace amounts in the seeds, where cyclolignans (aryltetralones) are by far the major components. In addition to hydroxy-otobain, only hydroxy-aryltetralones were detected in the seedlings, indicating a selective process in the translocation of secondary compounds. Copyright © 2000 John Wiley & Sons, Ltd.
Keywords: Cyclolignans; HPLC; Myristicaceae; Seedlings; Virola sebifera